2017
DOI: 10.1111/iep.12231
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of phenylbutyrate on glutamine, branched‐chain amino acid and protein metabolism in skeletal muscles of rats

Abstract: Phenylbutyrate (PB) acts as chemical chaperone and histone deacetylase inhibitor, which is used to decrease ammonia in urea cycle disorders and has been investigated for use in the treatment of a number of lethal illnesses. We performed in vivo and in vitro experiments to examine the effects of PB on glutamine (GLN), branched-chain amino acid (BCAA; valine, leucine and isoleucine) and protein metabolism in rats. In the first study, animals were sacrificed one hour after three injections of PB (300mg/kg b.w.) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…4 ). Unfortunately, it has been shown that phenylbutyrate activates the BCKD, resulting in decreases in BCAA and BCKA levels in blood plasma [ 55 , 56 ]. Marked decrease of BCAAs in UCD after phenylbutyrate treatment has been reported by Scaglia et al [ 57 ].…”
Section: Disorders With Decreased Bcaa Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ). Unfortunately, it has been shown that phenylbutyrate activates the BCKD, resulting in decreases in BCAA and BCKA levels in blood plasma [ 55 , 56 ]. Marked decrease of BCAAs in UCD after phenylbutyrate treatment has been reported by Scaglia et al [ 57 ].…”
Section: Disorders With Decreased Bcaa Levelsmentioning
confidence: 99%
“…Current treatment of MSUD is based on protein restriction and synthetic formulas with reduced BCAA content. Perspective may be phenylbutyrate, which activates BCKD and decreases BCAA and BCKA levels [ 55 , 56 ]. Unfortunately, studies examining phenylbutyrate in MSUD patients are unique.…”
Section: Disorders With Enhanced Bcaa Levelsmentioning
confidence: 99%
“…Recent random control trials using glycerol phenylbutyrate and sodium phenylbutyrate on patients who had two or more episodes of HE in the last 6 months indicated fewer recurrent episodes. Even though phenylbutyrate is well tolerated in adults with cirrhosis, it has been shown to decrease BCAA levels in blood plasma . This is probably due to enhanced glutamine depletion and removal from the body, which in turn activates BCAA catabolism.…”
Section: Treatment Of Hepatic Encephalopathymentioning
confidence: 99%
“…The more pronounced atrophy of white muscles is observed in muscle wasting disorders, and the responses of red muscles to STZ and/or MSC therapy may differ. 37 The infusion of MSCs in diabetic animals promoted a significant improvement in motor function and increased the number of muscle fibres in spite of the absence of significant changes in CSA. However, the observed strong positive correlation between CSA and motor activity is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of myofibres and muscle mass was associated with both increased protein degradation and decreased protein synthesis in skeletal muscles causing the muscle weakness in T1D. The more pronounced atrophy of white muscles is observed in muscle wasting disorders, and the responses of red muscles to STZ and/or MSC therapy may differ . The infusion of MSCs in diabetic animals promoted a significant improvement in motor function and increased the number of muscle fibres in spite of the absence of significant changes in CSA.…”
Section: Discussionmentioning
confidence: 99%